Balance of Green Open Space to Support Green Settlement in Yogyakarta Urban Area - Widodo Brontowiyono (Teknik Lingkungan Universitas Islam Indonesia, 2016)
The greatest problem relating to settlement growth in Yogyakarta urban area is the declining number of green open spaces. This study aimed to analyze the balance between the availability of and need for green open space development to promote the existence of green settlement in Yogyakarta urban area. The methods employed in this study were field research and studio analysis by referring to the related research methods previously conducted by the researcher as well as by the others. The results showed that the extent of green open space in Yogyakarta urban area reached 1,469.45 Ha or 16.2% of the total area. Therefore, the need for green open space lacked 13.8% of the total area. The general condition of the green open space was categorized as average in either housing clusters or settlements (non-housing clusters). Good condition was found only in low-density settlement, while poor condition of green open space was located in high-density settlement. The development of green open space should focus on public green open space while maintaining the private one. Some of the potential areas for this included rice fields, village treasury lands, riverbanks, roadsides, railway boundaries, public areas, and others.